Determining the optimal storage time and temperature for performing platelet function assays and global hemostasis assays. (3rd April 2022) - Denessen, E.J.S.; Van Den Kerkhof, D.L.; Jeurissen, M.L.J.; Wetzels, R.J.H.; Verhezen, P.W.M.; Henskens, Y.M.C
Abstract: Platelet function assays and global haemostasis assays are essential in diagnosing bleeding tendencies, with light transmission aggregometry (LTA) as golden standard. The Multiple Electrode Aggregation (Multiplate), platelet function assay (PFA) and rotational thromboelastometry (ROTEM) are mostly used as whole-blood screening tests. Currently, patients have to travel to specialized laboratories to undergo these tests, since specific expertise is required. Pre-analytical variables, like storage time and temperature during transport, are still considered to be the most vulnerable part of the process and may lead to discrepancies in the test results. We aim to give a first impression on the stability of blood samples from healthy volunteers during storage and investigate the effect of storage time (1, 3, 6 and 24 hours) and temperature (4°C, room temperature and 37°C) on the Multiplate, PFA, ROTEM and LTA test results. Our data indicated that, for the PFA, whole blood can be stored for 3 hours at room temperature. Whole blood used for the Multiplate and ROTEM can be stored for 6 hours of storage. For LTA, PRP and whole blood were stable up to 3 hours at 4°C or room temperature and 6 hours at room temperature, respectively.